Effect of coronary-caval shunt combined with partial pericardial devascularisation on oesophageal and gastric variceal bleeding caused by portal hypertension - Bai, Jigang; Xu, Meng; Wang, Ruitao; Mu, Yiping; Dong, Shunbin; Wu, Zheng; Wu, Shengli; Liu, Chang (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: To investigate the effect of coronary-caval shunt combined with partial pericardial devascularisation on oesophageal and gastric variceal bleeding caused by portal hypertension. Materials and Methods: Between January 2005 and January 2015, coronary-caval shunt operations combined with partial pericardial devascularisation were performed electively on 15 cirrhotic patients with portal hypertension. All of these patients had a history of oesophageal and gastric variceal bleeding. The clinical and follow-up data of these patients were reviewed retrospectively. Another 15 patients receiving non-surgical treatments in a similar follow-up period were used as controls to compare the preventive effects of different treatment strategies on rebleeding. Results: All of the 15 surgical procedures were performed successfully, and no severe complications occurred. Among these, autogenous splenic veins were used as bridge vessels in 6 cases, whereas the coronary vein and inferior vena cava were anastomosed directly in 9 cases. All surgical patients were followed up from 5 months to 10 years with an average of 63 months; 2 patients died due to liver failure induced by reactivation of hepatitis B virus and oesophageal/gastric variceal rebleeding, respectively. The rebleeding rates for surgical and non-surgical patients were 6.7% and 66.7% (p<0.05), respectively, whereas the 5-year survival rates for the two groups were 85.7% and 33.3% (p<0.05), respectively. Conclusion: Patients with oesophageal and gastric variceal bleeding caused by portal hypertension may benefit from a coronary-caval shunt combined with partial pericardial devascularisation due to decreased coronary vein pressure, unaffected hepatic blood inflow, and reduced incidence of rebleeding.